Study of heat transfer and friction loss of nanofluid suspension flow in circular pipe heat exchanger / Sandru Ramadas - Sandru , Ramadas (2020)
This stated experiment focused on the study of convective heat transfer and friction loss in a circular flow passage for Graphene oxide-based nanofluids which are consist of Graphene Oxide/Distilled water with their different wt. % concentrations. These GO/DW based nanofluids where been prepared by using a facile two-step method, while the GO particles were synthesized by a modified hummer method. Four different (0.025, 0.05, 0.075, and 0.1 wt. %) were produced by dispersing graphene particles in distilled water under high probe sonication. The GO/DW based nanofluids flowing in a horizontal shell and tube heat exchanger counter flow under turbulent flow conditions where been investigated for heat transfer, Nusselt numbers, pressure drop, and friction loss studies. The constant heat flux and varying flow rate conditions have been used to analyse the heat transfer improvement in a circular heat exchanger. The results show the convective heat transfer coefficient of the nanofluids is slightly higher than the base fluid at the same flow rate and the same inlet temperature. The heat transfer coefficient of the nanofluids increases with the increase of flow rate, also the heat transfer coefficient increases with the increase of the concentration of the nanofluids, however, an increase in the concentration causes the increase in the viscosity of the fluid leading to a slight increase in the friction loss. As for further analysis, distilled water where been compared with graphene oxide (GO/DW) base nanofluids to compare their heat transfer, Nusselt numbers, and pressure drop variations.